2020
DOI: 10.1002/gj.3937
|View full text |Cite
|
Sign up to set email alerts
|

Neo‐Tethyanslab tearing constrained by PalaeoceneN‐MORB‐like magmatism in southern Tibet

Abstract: Southern Tibet is a key region for investigating the magmatism that occurredduring the collision between India and Asia. The break‐off of the Neo‐Tethyan slab, after the onset of continental collision at ca. 65–60 Ma, affected the lithospheric thermal regime and led to a series of magmatic and tectonic events. Many magmatic rocks generated by slab break‐off have been reported in southern Tibet; however, which of these record the initial slab break‐off (i.e., slab tearing) is still an open question. The Lianxia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 95 publications
2
0
0
Order By: Relevance
“…During India-Asia continental collision, the subducted oceanic slab would have had a higher density than the passive continental lithosphere, so the subducted oceanic slab is likely to have become delaminated from the continental lithosphere after initial continental collision (Zhu et al, 2015). In such a situation, upwelling of deep mantle would have provided juvenile basaltic magmas to the overlying lower crust (Tian et al, 2021), which is consistent with the geochemical variations we observed in the Chacangka granitoids. The timing of slab breakoff has been well constrained at ca.…”
Section: Geological Implicationssupporting
confidence: 78%
See 1 more Smart Citation
“…During India-Asia continental collision, the subducted oceanic slab would have had a higher density than the passive continental lithosphere, so the subducted oceanic slab is likely to have become delaminated from the continental lithosphere after initial continental collision (Zhu et al, 2015). In such a situation, upwelling of deep mantle would have provided juvenile basaltic magmas to the overlying lower crust (Tian et al, 2021), which is consistent with the geochemical variations we observed in the Chacangka granitoids. The timing of slab breakoff has been well constrained at ca.…”
Section: Geological Implicationssupporting
confidence: 78%
“…57-50 Ma, on the basis of the presence of extension-related mafic dikes and contemporaneous felsic melts in the Lhasa Terrane (Huang et al, 2016, Huang, Rooney, et al, 2021W.-Q. Ji et al, 2009;Tian et al, 2021;Zhao et al, 2011;Zhu et al, 2015). The Chacangka granitoids that formed before and after slab breakoff have different chemical and isotopic compositions, which is consistent with the proposal that the source of magmas in the central Lhasa Terrane was influenced by a magmatic "flare-up."…”
Section: Geological Implicationssupporting
confidence: 75%